(untitled) (International Journal of Innovative Research in Computer Science & Technology, 2022)
Today the construction industry is in need of finding cost effective materials for increasing the strength of concrete structures. This project work emphasis on the study of using steel scrap in the innovative construction industry. Steel Scrap concrete is a concrete containing fibrous material that is uniformly distributed and casually oriented. This paper aims to have a comparative study between turn fiber, binding wire and steel nail in M25 concrete. The tests conducted were slump test, compressive strength test, split tensile strength test and for this concrete cubes, beams and cylinders were cast and cured and tests were done at 3rd day, 7th day and 28th day.